Rapidly progressive and fatal neurocutaneous melanosis presenting as recurrent headache. Issue 2 (16th April 2013) - Yamazaki, Yasuhiro; Matsuzawa, Tohru; Takasugi, Kazuo; Suzuki, Nozomu; Kanda, Makoto; Kobayashi, Ichiro
Abstract Neurocutaneous melanosis is an extremely rare disease characterized by large or multiple congenital melanocytic nevi and benign or malignant proliferation of melanocytes in the central nervous system. Neurological manifestations usually develop during the first three years of life and the prognosis of patients with NCM who manifest neurological symptoms is very poor. Here we describe a 9‐year‐old girl who manifested neurological symptoms caused by communicating hydrocephalus and died of proliferation of melanocytes in the central nervous system 11 months after the initial symptoms. Serum and cerebrospinal fluid 5‐S‐CD levels could be a useful marker of disease progression, even in patients with NCM without apparent malignant findings at initial biopsy.